Consequences of the Abandonment of Mandatory Joint Audit: An Empirical Study of Audit Costs and Audit Quality Effects. Issue 2 (3rd April 2017) - Lesage, Cédric; Ratzinger-Sakel, Nicole V. S.; Kettunen, Jaana
Abstract: This paper focuses on the unique Danish setting in examining the consequences of abandoning a mandatory joint audit regime. We study the effects on audit costs (measured by audit fees) and audit quality (measured by abnormal accruals) of the abandonment of the mandatory joint audit in Denmark in 2005. We perform our analysis on non-financial listed Danish companies for the 2002–2010 period. Our results show that a joint audit is associated with higher fees, but that the association between joint audit and abnormal accruals is insignificant. This suggests that the higher audit fees cannot be explained by higher audit quality. Our results are robust to alternative measurements of fees and audit quality. Additional analyses show that the fee premium related to a joint audit decreases over time and that the Big 4 concentration in our sample has increased since the switch from mandatory to voluntary joint audit. Our results are consistent with the motivations driving the regulatory change in Denmark and are of interest to regulators and actors in the audit market.